Болезни лососевых рыб при садковом выращивании. - Vismanis, K.O. (1978)
Three years data on salmonidae diseases study (rainbow trout, sea trout, coho salmon, pink salmon, and Baltic and steelhead trout) are represented in the article. In the time of salmonidae breeding in sea water the main danger lies in infectious vibrio disease with Vibrio anguillarum as its agent of infection. Considerably more rarely the infectious diplostomatosis desease occurs (agent of infection-Diplostomum sp.). During cage breeding of fish in fresh water lakes certain infective deseases, such as diplosto-mose, ergasilosis (agent of infection-Ergasilus sieboldi) and argulosis (agent of in-fection-Argulus foliaceus cause damage. Such parasites as Apiosoma sp., Epistylis sp., Chilodonella cyprini, Trichodina sp., Trichodinella sp., Ichthyophthirius multifiliis, Gyrodactylus sp., Cystidicola farionis, Piscicola geometra were met not so often. Besides, the diseases of nonparasitic character may be the cause of fishes death. Among them - avitaminosis and ceroid degeneration of the liver, arising as the result of usage of low-grade and defective feeds. 3. ausgabe des sonderheftes über fischereiliche untersuchungen der DDR und der UDSSR in der Ostsee. 3. выпуск совместного сборника научных статей по вопросам рыбохозяйственных исследований ГДР и СССР в Балтийском море. Published